An evaluation of rapid antigen tests diagnostic performance in the detection of SARS-CoV-2 infection (Annals of Medical Research, 2023)
Aim: The study aimed simultaneously compare the diagnostic performance of the rapid antigen test (CoVard COVID-19 Rapid Antigen Test Kit, Turkey) and the RT-PCR test used in the detection of SARS-CoV-2 infection.Materials and Methods: In this study, the results of rapid antigen tests and RT-PCR tests applied simultaneously to the diagnosis of SARS-CoV-2 infection on nasopharyngeal swab specimens taken from patients applying to the Mersin University Hospital Emergency Unit with various symptoms were retrospectively analyzed. The study included 308 patients with or without respiratory tract infection symptoms who underwent COVID-19 rapid antigen and RT-PCR testing.Results: It was observed that 157 (51.0%) of the patients had symptoms related to COVID-19. A total of 50 (16.2%; 95%CI: 12.0-20.5%) of the patients' rapid antigen test and 97 (31.5%; 95%CI: 26.3-37.0) of the patients' RT-PCR test were positive. The rapid antigen test for 41 (42.3%; 95%CI: 32.0-52.9) out of 97 specimens with a positive RT-PCR test was also positive. The rapid antigen test was positive in nine (18%; 95%CI: 8.6-28.6) specimens while the RT-PCR test was negative. The concordance between the rapid antigen test and the RT-PCR was intermediate (k=0.437, p
Keywords: COVID-19; RT-PCR; Rapid antigen test; Concordance